Terpenes from Aristolochia triangularis - Lopes, Lucia M.X. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Trevisan, Lígia M.V. [UNESP]; Grigolli, Tania M. [UNESP] (Elsevier B.V., 1990)
Phytochemical examination of Aristolochia triangularis led to the isolation of allantoin, nerolidol, sitosterol, dibenzylbutyrolactone type lignans and ent-kaurane type diterpenes. This is the first report on the isolation of ent-kaurane from a natural source. © 1990.
Keywords: Allantoin; Aristolochia triangularis; Aristolochiaceae; Kaurane diterpenes.; Nerolidol; Sitosterol